2017
DOI: 10.1002/2016jd026368
|View full text |Cite
|
Sign up to set email alerts
|

Lidar observations of stratospheric gravity waves from 2011 to 2015 at McMurdo (77.84°S, 166.69°E), Antarctica: 1. Vertical wavelengths, periods, and frequency and vertical wave number spectra

Abstract: Five years of atmospheric temperature data, collected with an Fe Boltzmann lidar by the University of Colorado group from 2011 to 2015 at Arrival Heights, are used to characterize the vertical wavelengths, periods, vertical phase speeds, frequency spectra, and vertical wave number spectra of stratospheric gravity waves from 30 to 50 km altitudes. Over 1000 dominant gravity wave events are identified from the data. The seasonal spectral distributions of vertical wavelengths, periods, and vertical phase speeds i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
74
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(93 citation statements)
references
References 107 publications
12
74
2
Order By: Relevance
“…These results are consistent with the results from previous studies in the Antarctic region (Kaifler et al, 2015;Kogure et al, 2017;Liu et al, 2014;Zhao et al, 2017). This value increased by 2-3 times at each 10 km of altitude increase between 40 and 60 km altitudes, and the winter (June to August) mean values at each altitude were 2-3 times larger than those of the fall (March to April) and spring (October) periods.…”
Section: Resultssupporting
confidence: 92%
“…These results are consistent with the results from previous studies in the Antarctic region (Kaifler et al, 2015;Kogure et al, 2017;Liu et al, 2014;Zhao et al, 2017). This value increased by 2-3 times at each 10 km of altitude increase between 40 and 60 km altitudes, and the winter (June to August) mean values at each altitude were 2-3 times larger than those of the fall (March to April) and spring (October) periods.…”
Section: Resultssupporting
confidence: 92%
“…This finding is in accordance with lidar observations at McMurdo at z = 30–50 km that found that false|falseTfalse/trueT̄[[SPiwidetilde]]~|2 followed lognormal distributions with respect to | λ z | and τ r (Zhao et al, ). That, as well as the fact that Zhao et al () observed GWs with both upward and downward phase progression, suggests that some of the GWs observed at McMurdo at z = 30–50 km were likely secondary GWs created in the stratopause region (i.e., z ∼ 40–65 km) by body forces from primary GW dissipation (Becker & Vadas, ). This conclusion is supported by a recent high‐resolution wintertime model study at McMurdo using the GW‐resolving KMCM (Vadas & Becker, ).…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…In this section we analyze two cases where fishbone structures are seen in temperature data measured by an Fe Boltzmann temperature lidar at Arrival Heights (166.69°E, 77.84°S) near McMurdo, Antarctica (Chu et al, ; Chu, Huang, et al, ; Chu, Yu, et al, ). For the cases shown here, we derive the temperatures from the pure Rayleigh scattering region at z ∼ 30–70 km using the Rayleigh integration technique (Alexander et al, ; Chu et al, ; Fong et al, ; Kaifler et al, ; Klekociuk et al, ; Lu et al, , ; Wilson et al, ; Yamashita et al, ; Zhao et al, ). All lidar data used here have 1‐hr temporal resolution and 1‐km vertical resolution.…”
Section: Secondary Gws Within Fishbone Structures In Mcmurdo Lidar Datamentioning
confidence: 99%
“…Finally, several fishbone structures were identified in lidar data at McMurdo near the winter stratopause and were shown to contain secondary GWs (Vadas et al, ). As corroboration of these results, analysis of wintertime lidar data at McMurdo inferred that λ H of the GWs was much larger in the MLT than in the stratosphere (Chen et al, ; Chen & Chu, ; Zhao et al, ), in excellent agreement with model results (BV18; VB18).…”
Section: Introductionsupporting
confidence: 58%